2012
DOI: 10.1186/1471-2458-12-789
|View full text |Cite
|
Sign up to set email alerts
|

Neck/shoulder pain and low back pain among school teachers in China, prevalence and risk factors

Abstract: BackgroundSchool teachers represent an occupational group among which there appears to be a high prevalence of neck and/or shoulder pain (NSP) and low back pain (LBP). Epidemiological data on NSP and LBP in Chinese teachers are limited. The aim of this study was to investigate the prevalence of and risk factors for NSP and LBP among primary, secondary and high school teachers.MethodsIn a cross-sectional study of teachers from 7 schools, information on participant demographics, work characteristics, occupationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
194
11
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(266 citation statements)
references
References 38 publications
39
194
11
22
Order By: Relevance
“…These results are in agreement with other studies that evaluated basic education teachers, confirming that the school is a workspace with female predominance [15][16][17][18] . In the past 12 months, 48% of the teachers presented musculoskeletal symptoms (Table 2).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in agreement with other studies that evaluated basic education teachers, confirming that the school is a workspace with female predominance [15][16][17][18] . In the past 12 months, 48% of the teachers presented musculoskeletal symptoms (Table 2).…”
Section: Discussionsupporting
confidence: 83%
“…The parts of the body most affected by musculoskeletal symptoms were the knees, ankles and/or feet, neck, wrists/ hands and back (Table 2). Our results present a similarity with previous research in which the main musculoskeletal problems found in teachers are located in regions such as the back, neck, shoulders, wrists/hands, ankles and/or feet 17,20,21,24 . According to Shuai et al 4 , the characteristics of the teaching work, such as long time sat on tables and standing to write, frequent and prolonged reading sessions, preparing lessons and typing on the computer, associated with the biomechanical factors present in the activity of repetitive requirements and developed in ergonomically inadequate designed environments , result in musculoskeletal changes.…”
Section: Discussionsupporting
confidence: 72%
“…There was no statistically significant relationship between pain in neck, back, upper limb and classes per day, classes per week (Table 3) These results were similar to a study done in China about the relation between hours of work per week and MSDs , they detected that there were no association with both neck, shoulder ,low back pain and hours of work (Yue et al, 2012). These results contradicted with previous studies that found long weekly working hours expose teachers to factors such as prolonged standing, prolonged sitting or awkward posture all of which have been associated with back pain (Murthy & Mitra, 2015) There was no statistically significant relationship between pain in neck and or back, upper limb and lower limb with number of students in the class (Table 3).…”
Section: Discussionsupporting
confidence: 79%
“…According to the results obtained, the prevalence rates of sore neck and sore shoulder were the same, i.e., equal to 100%. This was higher than the findings reported by similar research in Sudan [12], China [13], New Zealand [9], and the Netherlands [15]. A body of research indicates that alternative keyboards can keep one's neck, shoulders, wrist and forearm in a neutral position and can, therefore, reduce the negative effects [15].…”
Section: Discussioncontrasting
confidence: 56%
“…Millions of computer users worldwide are susceptible to the risk of sore limbs. Previous body of research has showed a correlation between working on computer and the occurrence of such painful disorders [13,14].…”
Section: Introductionmentioning
confidence: 99%